Effects of Sargassumoligocystum and Padina australis extract on Adipogenesis and Adipolysis in 3T3-L1 Cells - Jaswir, I; Ahmad, H; Susanti, D; Bakhtiar, MT; Octavianti, F (Univ Putra Malaysia Press, 2024)
In recent years, the search for natural, safe and effective therapies for the management of obesity has become important. The present study investigated the potential of brown seaweeds Sargassum oligocystum and Padina australis from Malaysian waters as natural alternatives for the management of obesity. Both seaweeds were macerated using acetone at room temperature for ten hours. The S. oligocystum extracts (SE) and P. australis extracts (PE) were then applied to 3T3-L1 cells during the differentiation stage and during the mature stage of the adipocyte life cycle to assess the effects of extracts on adipogenesis and adipolysis. Application of SE at 12.5 and 50 mu g/ml to the cells decreased adipogenesis by 71.7%, and 84.8%, respectively, while cells treated with 12.5 and 50 mu g/ml PE showed 85.7%, and 89.0% adipogenesis respectively, compared to control. Application of SE and PE to mature lipid cells stimulated adipolysis and the release of glycerol into the culture media. Application of SE at 12.5 and 50 mu g mu g/ml in the cell media induced glycerol release by up to 88.6 and 93.0%, respectively, while PE increased glycerol release up to 92.9 and 95.6% respectively, compared to isoproterenol. This study demonstrates the potential of whole brown seaweed extracts from S. oligocystum and P. australis collected from Malaysian waters as natural anti-obesity agents. Incorporation of the brown seaweed into the diet as a functional food will be useful for prevention and treatment of obesity. (C) All Rights Reserved